KOEFISIEN RESTITUSI: MAKNA FISIS, FORMULA MATEMATIS, DAN REDUKSI DIDAKTIS - Dindin Nasrudin; Chaerul Rochman; Herni Yuniarti Suhendi (UIN Sunan Gunung Djati Bandung, 2017)
One of the physics matter that is considered difficult by high school students is the concept of collision in which discuss the coefficient of restitution (e). On that basis, the restitution coefficient becomes one of the studies discussed in Physics Depth II for pre-service physics teacher in one of LPTK in West Java. This paper describes the profile of pre-service physics teacher in understanding the physical meanings of restitution coefficients, how to write mathematical formulas and the appropriate didactic reduction in learning the concept of restitution coefficients in high school students. The population of this research is pre-service physics teacher in one of LPTK in West Java, while the sample is 80 pre-service physics teacher who has taken the subject of Physics Depth II. By using cross-sectional survey method, it was found that (1) the number of respondents who answered the physical meaning of the restitution coefficient in the right category were: 39.7%, the less appropriate category was 22% and the rest of the category was not exactly 38.3%. (2) The mathematical formula of the selected restitution coefficient is 91.3% using TYPE B1, 2.8% using TYPE B2 and the remaining 5.7% using TYPE B4. (3) The didactic reduction chosen by the respondents in learning the concept of restitution coefficient in high school students is 10.2% by returning to the qualitative mean, 66.7% using drawings and sketches, 20.3% using analogy, while the rest using particularization (1.4%) and generalization (1.4%).